2013
DOI: 10.1007/s11999-013-2929-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Dislocation of Dual-mobility Cups in Primary Total Hip Arthroplasty

Abstract: Background Dual-mobility (DM) cups were introduced to minimize the risk of THA dislocation. The overall rate of dislocation of DM cups (including both large and small articulations) is controversial and ranges from 0% to 5% in previous studies. Questions/purposes We therefore recorded (1) the dislocation rate, (2) loosening and osteolysis, and (3) subsequent related revisions with DM cups. Methods Between 1998 and 2003, 2480 primary THAs with DM cups were undertaken in 2179 patients. The mean age was 69 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(87 citation statements)
references
References 31 publications
(96 reference statements)
10
69
0
4
Order By: Relevance
“…Similarly, Combes at al. investigated 2480 primary THA with DMCs and reported 0.88% dislocation rate, which is far below the rates reported with conventional THA [14]. Similar results were observed in our current register study, where revision rates due to dislocation in DMCs were 0.7% compared with 2.4% in the Exeter group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, Combes at al. investigated 2480 primary THA with DMCs and reported 0.88% dislocation rate, which is far below the rates reported with conventional THA [14]. Similar results were observed in our current register study, where revision rates due to dislocation in DMCs were 0.7% compared with 2.4% in the Exeter group.…”
Section: Discussionsupporting
confidence: 86%
“…A p value < 0.05 was considered significant. In the case of bilaterally operations, both hips were included, but it has been reported that this has little effect on survival in register studies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dual mobility cups (DMC) were designed as a solution to reduce THA dislocation events [9,10]; the mobile polyethylene insert would diminish the occurrence of prosthetic neck impingement with the fixed cup and the large diameter articulation between the poly-ethylene component and the metallic acetabular component would increase the range of motion before dislocation [11,12]. Some complications were reported after the use of the first generation cups due to the premature wear of the polyethylene (intra-prosthetic dislocation), insufficient means of bony fixation and iliopsoas tendon impingement [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Dual-mobility acetabular cups [7,12,13,34] or constrained cups [17] can decrease the risk of dislocation and may be indicated in some patients whose risk of this complication is increased. However, studies up to now have not specifically analyzed the benefit of using these implants in patients with obesity as compared with standard implants in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%